Innovative Approaches to Developing Art Literacy in 8th–9th Grade Students - Bobomurodova Sojida Ablakulovna, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: This article explores innovative approaches to developing art literacy in 8th–9th grade students in secondary schools. It examines the role of interactive teaching methods, creative exercises, and mini-projects in enhancing students’ visual perception, compositional thinking, and aesthetic awareness. These methods encourage independent thinking, creative problem-solving, and artistic decision-making, helping students improve both practical skills and creative abilities.